Electromagnetic Scattering Characteristics of Composite Targets and Software Development Based on PO Algorithm - Wang, Chuanmo (My University, 2022)
Physical optics (PO) algorithm is a high-frequency electromagnetic (EM) algorithm, which is widely used to solve the EM scattering problems of electrically large composite targets. Due to the PO algorithm only considers the induced current in the bright region irradiated by EM wave, the computational memory and time consumption are superior than other high-frequency algorithms, and the calculation accuracy is pretty fine. Based on the PO algorithm, this thesis focuses on the occlusion judgement of PO algorithm and its application in composite targets. The main contents of this thesis are as follows: 1. The occlusion judgement software system for PO algorithm is developed. The main function of this software is to judge the bright region of the target under the irradiation of EM wave. This software uses two judgement methods: ray tracing method based on CPU and Z-Buffer method based on CPU and GPU. Moreover, due to the compromise between patch size and patch number, both methods have errors at the edge of bright and shadow regions. This thesis discusses the error and reduces it. 2. Based on PO algorithm, the EM scattering characteristics of targets covered by plasma sheath are discussed. We simulate the plasma sheath flow field data of hypersonic vehicle by FASTRAN software, compare and analyze the plasma sheath electron number density at different flight heights and speeds. On this basis, the bistatic RCS of hypersonic vehicle head-on irradiation under different flight heights and speeds is calculated by using the PO algorithm of layered medium. 3. SAR image simulation of tree ground composite target is carried out based on PO algorithm and Non-Uniform Fast Fourier Transform (NUFFT) method. Firstly, we introduce the geometric modeling and EM parameter modeling of tree ground composite target, and the scattering characteristics of tree ground composite target are obtained by using PO algorithm. Finally, the scattering field of the target is processed by NUFFT method, and the SAR simulation images of multiple trees scene are obtained.
Keywords: PO algorithm, EM Scattering, Z-Buffer frame cache, Plasma sheath, SAR image simulation